Analysis of Digitization of Zakat, Infaq, and Sadaqah in Alleviating Poverty in the Community at Baznas Medan City - Putri Septiyani; Eli Agustami; Abdul Rahman (Outline Publisher, 2026)
Purpose: This study aimed to develop a deep understanding of the social phenomena related to the digitalization of Zakat, Infaq, and Sadaqah (ZIS) distribution managed by BAZNAS Medan City, focusing on its social implications, such as improving transparency, efficiency, and community empowerment in poverty alleviation efforts. Method: The research employed a descriptive qualitative approach, collecting narrative data through in-depth interviews, participatory observation, and relevant documentation. The subjects of the study included institutions and individuals directly involved in the management of ZIS, such as administrators, program implementers, and beneficiaries. Purposive sampling was used to select informants who were considered to have the most relevant and insightful information. Data analysis followed the interactive analysis model proposed by Miles and Huberman, consisting of data reduction, data presentation, and conclusion drawing. To ensure data validity, triangulation techniques involving sources, methods, and time were applied. Results: The findings revealed that the digitalization of ZIS distribution led to positive social implications, contributing to greater transparency, efficiency, and empowerment in the fight against poverty.